Mesoporous carbon film via spin coating soft templating method for supercapacitor electrode. (18th May 2020) - Ali, Mahanim Sarif @. Mohd; Zainal, Zulkarnain; Hussein, Mohd Zobir; Wahid, Mohd Haniff; Chang, Sook-Keng; Fudzi, Laimy Mohd; Al-Zahrani, Asla Abdullah Meed
Mesoporous carbon (MPC) films were prepared by using spin coating self-assembly soft templating method onto titanium (Ti) foils as substrates. Carbon precursor of resorcinol (R), formaldehyde (F) and a surfactant of triblock copolymer Pluoronic F127 (F127) which may act as a structure directing agent (SDA) for the pore structure geometry tuning were used in the preparation of the mesoporous carbon films. The samples were then carbonised to obtain the final product of MPC films. The mesostructure was characterised by thermogravimetry (TGA), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) patterns, field emission scanning electron microscopy (FESEM) and electrochemical analyses. The MPC film showed excellent electrochemical property for supercapacitor application by achieving specific capacitance value of 15.23 mF cm -2 at the scan rate of 5 mV s −1 in 1.0 M potassium chloride (KCl) neutral aqueous electrolyte which was approximately 88 times higher than as prepared samples. F127/RF carbon film also displayed outstanding cycle stability with 98% capacitance retention after 1000 cycles. This has proven that the synthesised MPC film-coated titanium foil may be a promising candidate for high performance electric double layer capacitors (EDLC).